Key Factor Of Success in the Utilization of Enterprise Resource Planning as System Integration in the “Manufacturing Company of PT. XYZ” - Dehan Azzahrah Nurmahfudi; Wiwik Handayani (Green Inflation: International Journal of Management and Strategic Business Leadership, 2024)
Manufacturing companies are working hard to maximize the use of their information technology, especially on Enterprise Resource Planning (ERP) systems, in today's sophisticated, competitive, and technology-driven environment. By leveraging a central database and operating in a consistent system environment, ERP systems unify all company activities. This integrated system can combine information from multiple departments to make decision making easier and better suited to the internal and external needs of the business. The choice of an ERP system is an important investment intended to improve the financial, strategic and profitable performance of a company. This study clarifies the key factor of success faced by manufacturing companies while utilizing ERP software.